Inhibition or Promotion?-The Effect of Agricultural Insurance on Agricultural Green Development - Dainan Hou; Xin Wang; Xin Wang; Xin Wang; Xin Wang (Frontiers Media S.A., 2022)
Based on China's provincial panel data from 2007 to 2019, this article discusses the impact of agricultural insurance on agricultural green development, and discusses the issue of regional heterogeneity. This article first studies the impact mechanism of agricultural insurance on agricultural green development, calculates the agricultural green development index, and empirically analyzes the impact of agricultural insurance on agricultural green development. The empirical results show that agricultural insurance has an inhibitory effect on agricultural green development, and that the impact of agricultural insurance on agricultural green development in the three functional areas is heterogeneous. Finally, it puts forward countermeasures and suggestions to build a low-carbon subsidy mechanism for agricultural insurance, enrich agricultural insurance products, improve the coverage of agricultural insurance, and build an agricultural production mode of internal planting and breeding combined with recycling through policy incentives.